Asteroseismology and exoplanets : listening to the stars and searching for new worlds : IVth Azores International Advanced School in Space Sciences /: listening to the stars and searching for new worlds : IVth Azores International Advanced School in Space Sciences. (2017) - Unknown
No abstract available